A Study on Opinion of General Public over Mukhyamantri Mazi Ladki Bahin Yojya with reference to Nagpur City - Pandey, Pragati Richa (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Government of Maharashtra for the wellbeing of women introduced the Mukhyamantri Ladki Bahin Yojana for needy and poor women. The scheme is based on the objective of making women financial empowered by providing financial assistance of Rs. 1,500 per month. The benefits of the scheme is restricted to the women having annual family income below Rs. 2,50,000 and their age ranging from 18 years to 60 years. As per this scheme the eligible women get financial support to meet their daily expenses, healthcare facilities, education and personal expenses. The main objective of study is to know the scheme fully and also see the impact of the scheme on women of Maharashtra as well as to study the limitation of the scheme. This study is based on the 233 respondents selected randomly of Nagpur city who are the direct beneficiaries as well as non-beneficiaries. The primary data is collected from structured questionnaire, personal interviews and discussion with the respondents. The study is also based on the secondary data which has collected from the newspapers, online news, published research, Government websites etc. This research paper tried to cover all the parameter of the scheme and throw the light on opinions of the respondent about the scheme. In this paper the actual position of women like financial independency, financial empowerment, changes in financial status, undue advantages of scheme taken by some women, increasing the debts on state and effect on scheme on political party etc. are covered.